Synthesis of 1, 3-Alternate calic [4]-cyclen-benzo-crown-6 and its complexation with metal cations and organic molecules - Matinee Jamkratoke (Chulalongkorn University, 2007)
Thesis (M.Sc.)--Chulalongkorn University, 2000